2018
DOI: 10.1039/c7tb03090h
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared photothermal-responsive poly(vinyl alcohol)/black phosphorus composite hydrogels with excellent on-demand drug release capacity

Abstract: Novel PVA/pBP hydrogels with highly effective NIR-responsive drug release performance, robust mechanical properties and good biocompatibility were prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Indeed, phosphorus is an essential element constituting about 1% of total body weight in humans, primarily as a constituent of bone . A recent study reported that the addition of BP nanosheets leads to reinforcement of the tensile strength and compressive modulus of PVA hydrogels . Additionally, BP nanosheets can be easily oxidized and degraded into nontoxic phosphate ions, phosphate, and other PxOy species under physiological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, phosphorus is an essential element constituting about 1% of total body weight in humans, primarily as a constituent of bone . A recent study reported that the addition of BP nanosheets leads to reinforcement of the tensile strength and compressive modulus of PVA hydrogels . Additionally, BP nanosheets can be easily oxidized and degraded into nontoxic phosphate ions, phosphate, and other PxOy species under physiological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of both PTT of PEGylated BP nanosheets and chemotherapy of DOX triggered the remarkable tumor‐inhibited effect. Besides BP nanosheets as the nanocarrier, NIR photothermal effect of BP nanosheets timely contributed to the controlled release of drug . The thermal‐responsive BP@hydrogel nanostructures with DOX encapsulated inside displayed improved cancer therapy .…”
Section: Biomedical Application Of Nano‐bpmentioning
confidence: 87%
“…The photothermal conversion efficiency (PTCE) was calculated in accordance with the similar method described in Yang's report. [23] The photothermal performance of the CS/AM NSs hydrogels was investigated using the same method. Briefly, the CS/AM NSs hydrogels (diameter: 18 mm, thickness: 7 mm) were immersed in 3 mL of ultrapure water and irradiated with the NIR laser (power density: 1.5 W cm −2 ) for 10 min.…”
Section: Methodsmentioning
confidence: 99%